The contribution of a project-based learning course, designed as a pedagogy of practice, to the development of preservice teachers' professional identity. (April 2023) - Tsybulsky, Dina; Muchnik-Rozanov, Yulia
Abstract: This study demonstrates a positive link between participation in an online project-based learning course, designed as a pedagogy of practice, and preservice teachers' professional-identity development process. The linguistic and content analyses revealed that the construction of professional identity was manifested through six motifs: Self-confidence, self-agency, sense of belonging, self-awareness, autonomy, and envisioning a future teaching self. Each of the motifs was portrayed with its characteristic set of time-oriented types of discourse (i.e., using past, present, and future tenses while describing feelings and thoughts regarding one's teaching self.) Based on the findings, we introduce a multidimensional model that explains identity construction as occurring at the intersection between the dimensions of identity and the temporal dimensions found in reflective discourse. Highlights: This online project-based course contributed to PSTs' professional identity development. The study demonstrates the positive role of "pedagogy of practice" design on professional identity development. The positive contribution of the online PBL course was documented during COVID19 crisis. Six motifs related to PSTs' professional identity construction were discerned. Each of the motifs was portrayed with its characteristic set of tense-oriented types of discourse (past, present, future).